Association between volume of lung damage and endoplasmic reticulum stress expression among severe COVID-19 ICU patients - Renard, Domitille; Verdalle-Cazes, Mikael; Leprêtre, Perrine; Bellien, Jérémy; Brunel, Valery; Renet, Sylvanie; Tamion, Fabienne; Besnier, Emmanuel; Clavier, Thomas (Frontiers in Medicine, 2024)
Introduction Links have been established between SARS-CoV-2 and endoplasmic reticulum stress (ERS). However, the relationships between inflammation, ERS, and the volume of organ damage are not well known in humans. The aim of this study was to explore whether ERS explains lung damage volume (LDV) among COVID-19 patients admitted to the intensive care unit (ICU). Materials and methods We conducted a single-center retrospective study (ancillary analysis of a prospective cohort) including severe COVID-19 ICU patients who had a chest computed tomography (CT) scan 24 h before/after admission to assess LDV. We performed two multivariate linear regression models to identify factors associated with plasma levels of 78 kDa-Glucose-Regulated Protein (GRP78; ERS marker) and Interleukin-6 (IL-6; inflammation marker) at admission. Results Among 63 patients analyzed, GRP78 plasma level was associated with LDV in both multivariate models (β = 22.23 [4.08;40.38]; p = 0.0179, β = 20.47 [0.74;40.20]; p = 0.0423) but not with organ failure (Sequential Organ Failure Assessment (SOFA) score) at admission (r = 0.03 [−0.22;0.28]; p = 0.2559). GRP78 plasma level was lower among ICU survivors (1539.4 [1139.2;1941.1] vs. 1714.2 [1555.2;2579.1] pg./mL. respectively; p = 0.0297). IL-6 plasma level was associated with SOFA score at admission in both multivariate models (β = 136.60 [65.50;207.70]; p = 0.0003, β = 193.70 [116.60;270.90]; p < 0.0001) but not with LDV (r = 0.13 [−0.14;0.39]; p = 0.3219). IL-6 plasma level was not different between ICU survivors and non-survivors (12.2 [6.0;43.7] vs. 30.4 [12.9;69.7] pg./mL. respectively; p = 0.1857). There was no correlation between GRP78 and IL-6 plasma levels (r = 0.13 [−0.13;0.37]; p = 0.3106). Conclusion Among severe COVID-19 patients, ERS was associated with LDV but not with systemic inflammation, while systemic inflammation was associated with organ failure but not with LDV.